2022
DOI: 10.3389/fimmu.2022.981440
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast induces beneficial behavioral outcomes and reduces inflammation in male and female rats

Abstract: BackgroundAccumulative data links inflammation and immune dysregulation to the pathophysiology of mental disorders; little is known regarding leukotrienes’ (LTs) involvement in this process. Circumstantial evidence suggests that treatment with leukotriene modifying agents (LTMAs) such as montelukast (MTK) may induce adverse neuropsychiatric events. Further methodic evaluation is warranted.ObjectiveThis study aims to examine behavioral effects, as well as inflammatory mediator levels of chronic MTK treatment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 144 publications
0
7
0
Order By: Relevance
“…This case report provided significant insights, an imbalance in the Th1/Th2 immune response might compromise the body's defense mechanisms against specific viral, bacterial, and parasitic pathogens, potentially heightening the risk of opportunistic infections[ 19 ]. Patients with rheumatic diseases are frequently treated with biologicals, such as anti-TNF, which increases susceptibility to opportunistic infections[ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This case report provided significant insights, an imbalance in the Th1/Th2 immune response might compromise the body's defense mechanisms against specific viral, bacterial, and parasitic pathogens, potentially heightening the risk of opportunistic infections[ 19 ]. Patients with rheumatic diseases are frequently treated with biologicals, such as anti-TNF, which increases susceptibility to opportunistic infections[ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The systemic anti-inflammatory effects of MTK have long been of interest. Studies have found that MTK’s anti-inflammatory and antioxidant properties improve brain dysfunction and defects, and enhance the survival of neurons under oxidative conditions [ 9 , 10 , 11 ]. Research to date has shown that MTK may provide neuroprotection to alleviate central system disorders, such as Parkinson’s disease, Alzheimer’s disease, and epilepsy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB regulates gene expression in the arachidonic acid-eicosanoid pathway, including the inflammation-associated enzymes 5-lipoxygenase (LOX) [41] and cyclooxygenase (COX)-2 [42,43]. 5-LOX catalyzes the formation of leukotrienes (LTs)-inflammatory constituents involved in various immune-inflammatory-allergic responses [44,45]. One of the most active LTs in mammalian tissues is LTB4; it facilitates the immune response by activating leukocytes and acting as a potent pro-inflammatory mediator in peripheral tissues and the brain [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…5-LOX catalyzes the formation of leukotrienes (LTs)-inflammatory constituents involved in various immune-inflammatory-allergic responses [44,45]. One of the most active LTs in mammalian tissues is LTB4; it facilitates the immune response by activating leukocytes and acting as a potent pro-inflammatory mediator in peripheral tissues and the brain [45,46]. COX-2 catalyzes arachidonic acid to produce prostaglandins (PGs) [45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation